Манипулятивная составляющая социального взаимодействия в контексте политического маркетинга - Купцов, А. (Социология: теория, методы, маркетинг, 2004)
The article is devoted to analysis of manipulation aspects of social interaction within political marketing context. The author considers the concept of manipulation, shows the specific of sociological approach in this field. The main problem is the relation of manipulation in electoral process in Ukraine with the democratic changes of the Ukrainian political culture during the last decade. Special attention is paid to con sideration of the mass media role, problems of Ukrainian information space, potentials of manipulation component within election campaigns. The main conclusion is that the usage of manipulative technologies makes possibilities of political marketing more sizable, but influences perspectives of democracy in Ukraine. The author's view may be interesting for scholars in the field of politics, mass communications and social psychology.